2023
DOI: 10.1371/journal.pone.0291451
|View full text |Cite
|
Sign up to set email alerts
|

Patient-level explainable machine learning to predict major adverse cardiovascular events from SPECT MPI and CCTA imaging

Fares Alahdab,
Radwa El Shawi,
Ahmed Ibrahim Ahmed
et al.

Abstract: Background Machine learning (ML) has shown promise in improving the risk prediction in non-invasive cardiovascular imaging, including SPECT MPI and coronary CT angiography. However, most algorithms used remain black boxes to clinicians in how they compute their predictions. Furthermore, objective consideration of the multitude of available clinical data, along with the visual and quantitative assessments from CCTA and SPECT, are critical for optimal patient risk stratification. We aim to provide an explainable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 72 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…Several studies have proven the role of AI in predicting cardiovascular events from SPECT/CT using clinical, MPI 27,28 , and CTAC data. 29,30 Nevertheless, only a limited number of CTAC findings, like CAC 29 , or EAT 10 were included in these previous analyses. More recently we demonstrated that deep learning cardiac chamber volumes (from CTAC) provided incremental and complementary value to CAC and SPECT variables.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have proven the role of AI in predicting cardiovascular events from SPECT/CT using clinical, MPI 27,28 , and CTAC data. 29,30 Nevertheless, only a limited number of CTAC findings, like CAC 29 , or EAT 10 were included in these previous analyses. More recently we demonstrated that deep learning cardiac chamber volumes (from CTAC) provided incremental and complementary value to CAC and SPECT variables.…”
Section: Discussionmentioning
confidence: 99%